How the Marsden Fund has failed to achieve its full potential in the ESA panel: evidence of limitations in scope, biased outcomes, and futile applications - Bryan, Karin; Lowe, David (New Zealand Science Review, 2014)
We have analysed the scope of proposals funded by the ‘Earth Sciences and Astronomy’ (ESA) panel of the Marsden Fund for the period 2004 to 2013. The scope of proposals funded is very limited and does not reflect the full remit of the panel: the successful projects fail to encompass the quality and quantity of research being undertaken within the Earth sciences community in New Zealand, and a number of sub-disciplines that seek to address fundamental and important problems within the Earth sciences are largely excluded. Moreover, nearly 50% of the funded proposals for the past decade have been made to just two institutions. To address these limitations, we suggest that: (1) a review is undertaken to examine and widen the scope of the panel to encompass sub-disciplines that demonstrably are never or rarely funded; (2) the composition of panel members be examined and modified to reflect a much wider scope of sub-disciplines within the Earth sciences; and (3) a review of the wide discrepancies in funding distributions on an institutional basis be undertaken. We want to ensure that a more representative range of sub-disciplines, in keeping with modern and realistic definitions of the Earth sciences, is funded through this panel, and so we also recommend the formation of a new panel for ‘Environmental and Earth-system Sciences’ that could encompass the research involving modern-day processes so that applications in these sub-disciplines are not pointless. In addition, it is clear that a very substantial increase in funding to the Marsden Fund must be sought.